2018
DOI: 10.1016/j.physletb.2018.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Conformal structure of the heavy particle EFT operator basis

Abstract: An operator basis of an effective theory with a heavy particle, subject to external gauge fields, is spanned by a particular kind of neutral scalar primary of the non-relativistic conformal group. We calculate the characters that can be used for generating the operators in a non-relativistic effective field theory, which accounts for redundancies from the equations of motion and integration by parts. I. INTRODUCTIONIf one can say that a particle, and not its antiparticle, exists in the laboratory, then the len… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In Ref. [2] we showed that the operator basis in Ref. [1] is spanned by scalar primaries of the non-relativistic conformal group.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [2] we showed that the operator basis in Ref. [1] is spanned by scalar primaries of the non-relativistic conformal group.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…for a general velocity. 2 The Lagrangian in Eq. (3) can be rewritten now in terms of Q v and Q v , where now we will let Λ → M , as is conventional in heavy particle effective theory:…”
Section: Overview Of "Top Down" Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the effective field theory of the Goldstone mode, we compute the dimensions of operators to leading order in the angular momentum L and charge Q. We find a diverse set of scaling behaviors for NRCFTs in both d = 2 and d = 3.1 It is important to mention that Schrödinger symmetry is not simply the non-relativistic limit of the conformal symmetry but rather an entirely distinct algebra [15,16].2 It should be emphasized that this is not the only possibility. Ultimately the question "Given this NRCFT, what state of matter describes its large charge sector?"…”
mentioning
confidence: 96%
“…1 It is important to mention that Schrödinger symmetry is not simply the non-relativistic limit of the conformal symmetry but rather an entirely distinct algebra [15,16].…”
mentioning
confidence: 99%